Positive Emotional Attachment Influences Hedonic Shopping Motivation and Celebrity Endorsement on Impulse Purchase of Fashion Products on E-commerce in Java Island - Intan Sri Lestari; Supriyono; Reiga Ritomiea Ariescy (PT FORMOSA CENDEKIA GLOBAL, 2023)
Many factors can lead to impulsive buying actions. This study aims to analyze the effect of hedonic shopping motivation and celebrity endorsement on impulse buying with positive emotional attachment.This study uses primary data obtained from respondents' answers, namely consumers of fashion products in e-commerce on the island of Java. All existing respondents are stratified based on the region which includes: Banten, DKI Jakarta, D.I.Yogyakrta, West Java, Central Java, East Java. To fulfill the research objectives, the hypothesis was tested with SEM PLS. From the SEM PLS test, it can be concluded that: (1) Hedonic Shopping Motivation contributes to Impulse Buying, (2) Celebrity Endorsement contributes to Impulse Buying, (3) Hedonic Shopping Motivation generates positive emotions that contribute to Impulse Buying, (4) Celebrity Endorsement does not generate positive emotions that do not contribute to Impulse Buying, (5) Positive Emotions contribute to Impulse Buying.